LOW HIGH-DENSITY LIPOPROTEIN LEVEL ASSOCIATED WITH ENHANCED INFLAMMATORY RESPONSE AND ONE-YEAR PERSISTENCE OF LONG COVID IN PATIENTS UNDERGOING HEMODIALYSIS: A CROSS-SECTIONAL COHORT STUDY - Stepanova, Natalia; Driianska, Victoria; Rysyev, Andriy; Snisar, Lyudmila; Kolesnyk, Mykola (Eastern Ukrainian Medical Journal, 2024)
Background: Long-term consequences of COVID-19, known as long COVID, present distinctive hurdles for patients receiving hemodialysis treatment. Reduced levels of high-density lipoprotein (HDL) (< 1.22 mmol/L) have previously been demonstrated to be associated with heightened susceptibility to COVID-19 and immediate COVID-19-related adverse outcomes in this patient population. However, the potential association between HDL levels and the persistence of long COVID has not been examined within the hemodialysis cohort. The present study aimed to explore the relationship between HDL levels and inflammatory responses one year after COVID-19 among patients undergoing hemodialysis. Methods: A total of 80 patients treated with hemodialysis, aged 55 (44-62.5) years, with a dialysis vintage of 45 (21-78.6) months and a history of COVID-19, were enrolled in this cross-sectional cohort study. Among them, 45 (56.2%) were diagnosed with long COVID, while 35 (43.8%) had fully recovered. Lipid profiles and inflammatory markers, such as serum C-reactive protein, and interleukins -6 and -17, were assessed one year post-infection. Results: Patients experiencing long COVID exhibited significantly lower HDL levels compared to fully recovered individuals: 1.19 (1.06-1.76) vs 1.66 (1.32-1.92) mmol/L (p < 0.0001). The HDL cut-off point of less than 1.22 mmol/L demonstrated a sensitivity of 84.9% and specificity of 95.3% to predict one-year long COVID persistence in our cohort. Among the patients with HDL levels < 1.22 mmol/L, elevated concentrations of C-reactive protein (р = 0.003), interleukin-6 (p = 0.005), and interleukin-17 (p < 0.0001) were evident compared to those with HDL concentrations exceeding 1.22 mmol/L. Subsequent subgroup analysis revealed a more pronounced inflammatory profile in patients concurrently experiencing long COVID and exhibiting low HDL levels. Conclusion: The obtained results suggest that a low level of HDL (< 1.22 mmol/L) may exacerbate the inflammatory response in patients undergoing hemodialysis, potentially contributing to the persistence of long COVID even a year after infection. Future research is necessary to elucidate the pathogenetic mechanisms of this relationship and explore potential strategies to improve patient outcomes.